Trichoderma koningiopsis (Hypocreaceae) has the smallest mitogenome of the genus Trichoderma - Castrillo, María Lorena; Bich, Gustavo Ángel; Amerio, Natalia Soledad; Barengo, Marcela Paola; Zapata, Pedro Darío; Saparrat, Mario Carlos Nazareno; Villalba, Laura Lidia (Frontiers in Microbiology, 2023)
The complete mitochondrial genome sequence of the mycoparasitic fungus Trichoderma koningiopsis was determined using the Illumina next-generation sequencing technology. We used data from our recent Illumina NGS-based project of T. koningiopsis genome sequencing to study its mitochondrial genome. The mitogenome was assembled, annotated, and compared with other mitogenomes. T. koningiopsis strain POS7 mitogenome is a circular molecule of 27,560 bp long with a GC content of 27.70%. It harbours the whole complement of the 14 conserved mitochondrial protein-coding genes (PCG) such as atp6, atp8, atp9, cox1, cox2, cox3, cob, nad1, nad2, nad3, nad4, nad4L, nad5, and nad6, also found in other Hypocreales. The mitogenome also contains two ribosomal RNA genes and 26 transfer RNA genes (tRNAs), 5 of them with more than one copy. Other genes also present in the assembled mitochondrial genome are a small rRNA subunit and a large rRNA subunit containing ribosomal protein S3 gene. A phylogenetic analysis was done using the 14 PCGs genes of T. koningiopsis strain POS7 mitogenome to compare them with those from other fungi of the Subphyla Pezizomycotina and Saccharomycotina. T. koningiopsis strain POS7 was clustered together with other representatives of Trichoderma lineage, within the Hypocreales group, which is also supported by previous phylogenetic studies based on nuclear markers. The characterization of mitochondrial genome of T. koningiopsis contributes to the understanding of phylogeny and evolution of Hypocreales.